A Survey of using Data Mining Techniques for Soil Fertility - Kommineni, Madhuri; Perla, Someswari; Bharathi Yedla, Divya (International Journal of Engineering and Technology, 2018)
Data Mining is a technique which focuses on large data sets to extract information for prediction and discovery of hidden patterns.Â  Data Mining is applicable on various areas like healthcare, insurance, marketing, retail, communication, agriculture. Agriculture is the backbone of countryâ€™s economy. It is the important source of livelihood. Agriculture mainly depends on climate, topography, soil, biology. Agricultural Mining is a technology which can bring knowledge to agriculture development. Data Mining in agriculture plays a role in weather forecasting, yield prediction, soil fertility, fertilizers usage, fruit grading, plant disease and weed detection. The current study presents the different data mining techniques and their role in context of soil fertility, nutrient analysis.Â